More than 30 years of 'Landcare' in Australia: five phases of development from 'childhood' to 'mid-life' (crisis or renewal?). Issue 4 (2nd October 2018) - Robins, Lisa
ABSTRACT: This article describes the five major development phases of Landcare in Australia – from its 'childhood phase' beginnings in the mid-1980s to its current day 'mid-life phase'. The 'Landcare approach' in its contemporary form is articulated in the Australian Framework for Landcare 2010–2020 as comprising the Landcare ethic, the Landcare movement founded on stewardship and volunteers, and the Landcare model . There is much evidence to substantiate the pivotal role Landcare has played in stimulating and enabling knowledge sharing, learning and on-ground action across Australia in the arena of natural resource management (NRM); and also to conclude that its potential for contributing to broader impacts, especially landscape-scale change, has been seriously hindered by various ill-conceived and/or executed policy settings and related institutional arrangements. Nevertheless, the Landcare approach (with its consistently sound ethic and movement, but with its model imperfections at different times) has proven itself robust. The time is now ripe for a new phase of Landcare driven by an alliance of its networks with Australia's 56 regional NRM organisations, backed by national non-governmental organisations, which cuts through the current political disengagement with NRM policy and practice and restores the centrality of and nationwide commitment to the Landcare approach.